Effect of micronutrient supplements on nutritional status of infants in Gaza Strip, Palestine - Albelbeisi, Ali H.A (2018)
Growth faltering is a common form of undernutrition in developing countries. Micronutrients deficiency including vitamin A, vitamin D, iron, and zinc has been associated with growth retardation in young children. This study aims to determine the impact of micronutrient powder supplementation on the nutritional status of infants in Gaza Strip, Palestine. The study was conducted in two phases. In phase one, a retrospective cohort study involving 2650 children from five primary health clinics was carried out to assess the growth patterns from birth to 24 months as to provide support for timing of micronutrient supplementation for phase two. In phase two, a prospective parallel randomized controlled trial was conducted with 200 infants aged six months being randomly selected from two United Nations Relief and Works Agency (UNRWA) clinics. The infants were randomly assigned into two groups: control (received National Micronutrient Supplement) and experimental (received Micronutrients powder for 12 months with National Micronutrient Supplement). The primary outcomes measured were weight, length, circumferences of head, waist and mid upper arm, triceps and subscapular skinfolds and hemoglobin of children, while the secondary outcomes included children’ dietary intakes and child feeding practices of mothers. Analysis in phase one was based on descriptive statistics, whereas Student’s t-test and General Linear Model (GLM) for repeated measures were used in phase two (based on a per protocol analysis). In the process of phase two, 18 and 12 participants dropped out of the experimental and control groups, respectively. The results of phase one indicated that faltering in length was more pronounced than weight faltering. From 6 to 24 months, while the prevalence of underweight was relatively stable (~ 5%), there was a decreasing trend in the prevalence of wasting (10 – 2.8%) but an increasing trend for stunting prevalence (9 – 20.4%). At the end of the study, the experimental group had a significant increase in all anthropometric measures except length-for-age and triceps skinfold-for-age z scores. Whereas, the control group showed a significant increase in weight, length, circumferences of head,waist, and mid upper arm-for-age, and subscapular skinfold-for-age z scores only. In both groups, a significant increase was observed in most nutrients (except fat and iron intakes), but a significant decrease in hemoglobin. The overall group effect was observed in hemoglobin, vitamin D intake, and all anthropometric measures except body mass index-for-age, head circumference-for-age, and subscapular skinfold-forage z scores with higher mean in the experimental group as compared to the control group. The changes in hemoglobin, carbohydrate, protein, and vitamin D intakes, and most of anthropometric measures (except head circumference-for-age, waist circumference-for-age, mid upper arm circumference-for-age, and subscapular skinfold-for-age z scores) showed a significant group by time interaction with a higher increment in the experimental group as compared with the control group (except triceps skinfold-for-age z score and protein intake). Moreover, the reduction in hemoglobin was significantly lower in the experimental group than that in the control group. At the end of the study, the experimental group had significantly lower proportions of anemia (11.4% vs. 52.3%, p < 0.001) and stunting (1.2% vs. 18.3%, p < 0.05) than the control group. In conclusion, micronutrient powder was found to have beneficial effects on anthropometric and biochemical measures of under-two children in this study. However, more studies are needed to better understand the contribution of micronutrient powder supplementation to energy and nutrient intakes. The findings also suggested that the addition of micronutrient powder supplements to the Ministry of Health supplementation protocol could improve the nutritional status of young children.